2010
DOI: 10.1007/s00442-010-1565-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental constraints on oviposition limit egg supply of a stream insect at multiple scales

Abstract: Species with complex life cycles pose challenges for understanding what processes regulate population densities, especially if some life stages disperse. Most studies of such animals that are thought to be recruitment limited focus on the idea that juvenile mortality limits the density of recruits (and hence population density), fewer consider the possibility that egg supply may be important. For species that oviposit on specific substrata, environmental constraints on oviposition sites may limit egg supply. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 63 publications
1
76
1
Order By: Relevance
“…Our findings are consistent with ''habitat constraints'' to recruitment, instead of ''supply determination'' (sensu Schmitt and Holbrook 2000) of adult female supplies at least in fishless streams, which translated to recruitment limitation of population sizes of first stage larvae. Similar cases of recruitment limitation by environmental or habitat constraints have been observed in other aquatic insects (Fincke 1994, Fonseca and Hart 2001, Spencer et al 2002, Lancaster et al 2010, and more commonly in marine fishes and terrestrial organisms (Price et al 1998, Connell andGreen 2000). A model presented by Lancaster et al (2010) suggested that mayfly egg supply (recruitment limitation) caused by environmental constrains (emergent rocks) is scale-dependent.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Our findings are consistent with ''habitat constraints'' to recruitment, instead of ''supply determination'' (sensu Schmitt and Holbrook 2000) of adult female supplies at least in fishless streams, which translated to recruitment limitation of population sizes of first stage larvae. Similar cases of recruitment limitation by environmental or habitat constraints have been observed in other aquatic insects (Fincke 1994, Fonseca and Hart 2001, Spencer et al 2002, Lancaster et al 2010, and more commonly in marine fishes and terrestrial organisms (Price et al 1998, Connell andGreen 2000). A model presented by Lancaster et al (2010) suggested that mayfly egg supply (recruitment limitation) caused by environmental constrains (emergent rocks) is scale-dependent.…”
Section: Discussionmentioning
confidence: 56%
“…Similar cases of recruitment limitation by environmental or habitat constraints have been observed in other aquatic insects (Fincke 1994, Fonseca and Hart 2001, Spencer et al 2002, Lancaster et al 2010, and more commonly in marine fishes and terrestrial organisms (Price et al 1998, Connell andGreen 2000). A model presented by Lancaster et al (2010) suggested that mayfly egg supply (recruitment limitation) caused by environmental constrains (emergent rocks) is scale-dependent. Future studies comparing outcomes at different spatial scales would be fruitful for testing that hypothesis; and new empirical scaling applications might be useful for unraveling the population level effects of recruitment (Lancaster et al 2010) and post-recruitment processes (Englund and Leonardsson 2008) acting at different scales.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations